The Malaysian Journey : Progress in Diversity. - Richter, Frank-Jurgen (Marshall Cavendish International (Asia) Ptd Ltd., 2003)
The Malaysian Journey is a most timely publication on Malaysia, as Prime Minister Mahathir bin Mohamad, one of the world's great contemporary leaders, left office in late 2003. The book captures Malaysia's transformation from a former British colony to one of Asia's most developed countries. At the same time, it provides an assessment of the key challenges facing Malaysia. The book, which discusses Malaysia's future, is suitable for policy-makers, business leaders, researchers and students at tertiary institutions, as well as anyone who is interested to know more about one of Southeast Asia's.